Awareness and Practice regarding Breast Cancer Screening among Women Residing at Bharatpur-7, Chitwan (Nepalese Journal of Cancer, 2026)
Background: Breast cancer is one of the leading causes of death among women worldwide. Early detection through screening techniques, increasing awareness related to breast cancer and implementing preventive practices can reduce its impact. The objective of the study was to find out awareness and evaluate the practice of breast cancer screening among women residing at Bharatpur Metropolitan City.Materials and Methods: A descriptive cross- sectional study design was carried out among 103 women by using non-probability purposive sampling technique from 5 toles of ward no. 7 of Bharatpur Metropolitan. Data were collected by using a structured interview schedule. Collected data was interpreted by using descriptive and inferential statistics and analysed by using SPSS version 22.Findings: Mean age of the respondents was 38.95 year. Nearly one third (29.1%) were of age group of 30- 39 years and majority (92.2%) respondents followed Hindu religion while (72.82%) belongs to Brahmin/ Chhetri. Likewise, only (6.8%) respondents had family history of cancer. The study findings further summarized the level of awareness into three categories where more than half (68.0% ) of the respondents had moderate, only (9.7%) had poor level, whereas (22.3%) had good level of awareness regarding breast cancer screening whereas nearly half (45.6 %) had poor practice and more than half (54.4%) had good practice of breast self-examination. Likewise, Educational level (0.039) of respondent was significantly associated with level of awareness at p ≤0.05.Conclusions: In conclusion, most of the respondents had moderate level of awareness and good level of practice regarding breast cancer screening however the concerned authorities should plan and conduct awareness programs to further minimize risks and enhance the existing awareness regarding breast cancer screening.